Is the reference desk used for reference interviews. Issue 1 (8th February 2021) - Bøyum, Idunn; Byström, Katriina; Pharo, Nils
Abstract : Purpose: The purpose of this study is to investigate why users turn to the university library's reference desk and whether librarians make use of the opportunity to conduct reference interviews to disclose any unexpressed information needs. Design/methodology/approach: This paper presents the results from a qualitative exploration study where interactions between librarians and users were observed in authentic situations at the reference desk and analyzed using a modified version of Radford and Connaway's (2013) categorization of inquiries. Findings: Most inquiries were seemingly easy to answer and pertained to collections and procedures in the library. Lending out desk supplies accounted for a high proportion of the activity. Only a small number of requests were subject-oriented and reference interview techniques were only used in 5% of the recorded inquiries. This means that the users' information needs were not probed in the vast majority of the interactions. Research limitations/implications: The study is exploratory and mirrors the activity that takes place in one specific library. The low number of reference interview techniques used may indicate a lack of interest in users' information needs, which signifies a risk of the reference desk being reduced to an arena for instrumental and superficial interaction between librarians and users. Originality/value: This study illustrates current developments in work at a physical library desk. Few recent studies address face-to-face interactions between librarians and users.